West Papua Culture-Based Virtual Youtuber Avatar Design with animated rigging on live2D Cubism - Dinda Reza Safitri; Mahendra Wibawa (IC-ITECHS, 2022)
Recent technological developments have opened up a golden opportunity for the world to see Papuan culture in Indonesia. Currently, virtual YouTubers are idols and brand ambassadors, but there are still no virtual YouTubers with West Papua's unique culture. The purpose of designing a virtual YouTuber avatar based on West Papuan culture is to create a virtual character that can represent West Papuan culture so that we can add alternative Indonesian YouTuber virtual characters, especially those with West Papuan aspect. is directed toward Papuan culture to national and international range. With its unique West Papuan culture, this character design mockup needs to be animated before entering the Youtuber's virtual world. Rigging or bone attachment animations are created in the Live2D Cubism Software and moved using face tracking technology in the Vtube Studio Software.